Stability and Expression of Selected miRNAs, circRNAs, and rRNAs in Swiss Albino Mice Tissues to Preditc Port-Mortem Interval - Onyekachi Ogbonnaya Iroanya; Tochukwu Frank Egwuatu; Adedolapo Meshach Adebajo; Solomon Tornnee Aloku; David Chima Uche; Stephania Semiire Folorunso (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics)
In forensics, post-mortem interval (PMI) estimation is essential. Researchers have devised various approaches to accurately determine PMI, consequently, ribonucleic acid (RNA) molecules could be useful PMI estimation tool. This study aims to ascertain the stability and expression of some ribosomal RNAs, micro-RNAs, and circular-RNAs in rat post-mortem liver, heart and muscle tissues. Fifty healthy adult Swiss albino mice were divided into five groups, sacrificed and target tissues were harvested. These genes- miR-122, 18S, miR-133a, RPS18, Circ-LRP6, 5S rRNA, Circ-AFF1, Circ-Ogdh, LC-Ogdh, U6 and GAPDH- were selected for the study. Extracted RNA was subjected to spectrophotometric analysis, complementary Deoxyribonucleic acid (cDNA) synthesis and amplified by Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) using gene-specific primers. For liver samples, miR-122 and 5S had the highest and lowest Cq-values respectively. There was a significant difference between the expression of GAPDH and Circ-Ogdh and 5S (p≤0.05). For the heart and muscle samples, miR-122 and Circ-LRP6 had the highest Cq-value respectively. In the heart, there was significant difference between the expression of GAPDH and miR-122, miR-133a and RPS-18 (p≤0.05).  In muscle tissue, there was significant difference between the expression of GAPDH and U6, Circ-AFF1 and Circ-LRP6 (p≤0.05). This study shows that miR-122 and LC-Ogdh (liver tissues), miR-122, miR-133a and Cir-LRP6 (heart tissues), and miR-122 and Circ-AFF1 (muscle tissues) are suitable reference genes for PMI estimation using GAPDH as a reference gene. In conclusion, a forensic method for PMI assessment may use a combination of tissue-specific miRNAs, ribosomal RNAs, SnRNAs, CircRNAs, and CircRNA+mRNA.